Current trends, methods and results of brown mustard (Brassica juncea) and black mustard (Brassica nígra) breeding - V. S. Trubina (Труды по прикладной ботанике, генетике и селекции, 2020)
Background. Various types of mustard and its forms differ significantly from each other in a set of morphological, biological, biochemical and other economically important traits. Both brown and black mustard are in great demand.Materials and methods. The study was conducted in 2009– 2018 on the brown mustard cultivar ‘Rosinka’ using the VNIIMK techniques. Promising cultivars of brown mustard (‘Zolushka’, ‘Nika’, ‘Yunona’) and black mustard (‘Niagara’) as well as source material with good breeding prospects were evaluated for their economic significance.Results and discussion. Individual selection based on self-pollination in the seed production of brown mustard population cultivars was found to facilitate identification of high-yielding lines, promptly increase the yield of cultivars, isolate lines exceeding the initial population in oil yield, and obtain biotypes with unusual fatty acid composition. The best accessions demonstrated an increase of 1.0–2.9% in their oil content. Besides, the selected material had the yield at the same or higher level than the reference (on average, 3.22 t/ha). An increase of oil yield varied from 0.23 to 0.36 t/ha. The technique of recurrent individual selection of elite plants from interspecific hybrid populations with the use of selfpollination resulted in developing 3 brown mustard cultivars: ‘Zolushka’, ‘Nika’ and ‘Yunona’. One of the important trends in mustard breeding is the development of cultivars with a high content of allyl mustard oil. As a result of this work, a new brown mustard cultivar was developed (‘Gorlinka’). One of the representatives of the economically important Brassicaceae family is the black mustard. Its new cultivar ‘Niagara’ was developed by recurrent individual selection from accession k-2632 preserved in the collection of the Vavilov Institute of Plant Genetic Resources (VIR). In competitive trials ‘Niagara’ demonstrated an average yield at the level of 1.5–1.7 t/ha, and the oil content in seeds of 37.0–40.0%. Cv. ‘Niagara’ has a short growing season.